Selinexor inhibits growth of patient derived chordomas in vivo as a single agent and in combination with abemaciclib through diverse mechanisms - Walker, Christopher J.; Chang, Hua; Henegar, Leah; Kashyap, Trinayan; Shacham, Sharon; Sommer, Josh; Wick, Michael J.; Levy, Joan; Landesman, Yosef (Frontiers in Oncology, 2022)
Chordoma is a rare cancer that grows in the base of the skull and along the mobile spine from remnants of embryonic notochord tissue. The cornerstone of current treatments is surgical excision with adjuvant radiation therapy, although complete surgical removal is not always possible. Chordomas have high rates of metastasis and recurrence, with no approved targeted agents. Selinexor and eltanexor are selective inhibitors of nuclear export (SINE) that prevent the karyopherin protein exportin-1 (XPO1) from shuttling its cargo proteins through nuclear pore complexes out of the nucleus and into the cytoplasm. As cancer cells overexpress XPO1, and many of its cargos include tumor suppressor proteins and complexes bound to oncogene mRNAs, XPO1 inhibition can suppress oncogene translation and restore tumor suppressor protein activity in different cancer types. SINE compounds have exhibited anti-cancer activity in a wide range of hematological and solid tumor malignancies. Here we demonstrate the preclinical effectiveness of SINE compounds used as single agents or in combination with either the proteasome inhibitor, bortezomib, or the CDK4/6 inhibitor, abemaciclib, against various patient- derived xenograft (PDX) mouse models of chordoma, which included clival and sacral chordomas from adult or pediatric patients with either primary or metastatic disease, with either differentiated or poorly differentiated subtypes. SINE treatment significantly impaired tumor growth in all five tested chordoma models, with the selinexor and abemaciclib combination showing the strongest activity (tumor growth inhibition of 78-92%). Immunohistochemistry analysis of excised tumors revealed that selinexor treatment resulted in marked induction of apoptosis and reduced cell proliferation, as well as nuclear accumulation of SMAD4, and reduction of Brachyury and YAP1. RNA sequencing showed selinexor treatment resulted in differences in activated and repressed signaling pathways between the PDX models, including changes in WNT signaling, E2F pathways and glucocorticoid receptor signaling. This is consistent with SINE-compound mediated XPO1 inhibition exhibiting anti-cancer activity through a broad range of different mechanisms in different molecular chordoma subsets. Our findings validate the need for further investigation into selinexor as a targeted therapeutic for chordoma, especially in combination with abemaciclib.